2009
DOI: 10.1109/jproc.2009.2015470
|View full text |Cite
|
Sign up to set email alerts
|

The Expanded Very Large Array

Abstract: In almost 30 years of operation, the Very Large Array (VLA) has proved to be a remarkably flexible and productive radio telescope. However, the basic capabilities of the VLA have changed little since it was designed. A major expansion utilizing modern technology is currently underway to improve the capabilities of the VLA by at least an order of magnitude in both sensitivity and in frequency coverage. The primary elements of the Expanded Very Large Array (EVLA) project include new or upgraded receivers for con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…Previous studies have used the Very Large Array (VLA) to search for compact radio sources in the ONC (e.g., Felli et al 1993a;Zapata et al 2004a), and fluxes produced by those studies have been used to correct for free-free contamination in disk mass studies (e.g., Eisner et al 2008;Mann & Williams 2010;Mann et al 2014). The expanded capabilities of the VLA correlator (Perley et al 2009), now enable surveys of much higher sensitivity than were previously possible. More recent surveys have taken advantage of this increase in sensitivity to map star-forming regions, including the ONC at 4.5 and 7.5 GHz (Dzib et al 2013;Kounkel et al 2014;Forbrich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used the Very Large Array (VLA) to search for compact radio sources in the ONC (e.g., Felli et al 1993a;Zapata et al 2004a), and fluxes produced by those studies have been used to correct for free-free contamination in disk mass studies (e.g., Eisner et al 2008;Mann & Williams 2010;Mann et al 2014). The expanded capabilities of the VLA correlator (Perley et al 2009), now enable surveys of much higher sensitivity than were previously possible. More recent surveys have taken advantage of this increase in sensitivity to map star-forming regions, including the ONC at 4.5 and 7.5 GHz (Dzib et al 2013;Kounkel et al 2014;Forbrich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…JVLA (Perley et al(2009), Perley et al(2011) has begun providing exciting science results as demonstrated in data presented by many at this Symposium even before it reaches its full upgraded potential. The several order of magnitude increase in correlator capacity promises delivery of sensitive spectroscopy at high spectral and spatial resolution.…”
Section: Al Woottenmentioning
confidence: 98%
“…This versatility is necessary because the widths of spectral features are influenced by Doppler shifts, which are proportional to the rest frequencies of the lines and the velocities of the emitting atoms and molecules. The correlator of the upgraded VLA system (Perley et al 2009) is fundamentally an XF design, as is the ALMA system, following its digital filter (Escoffier et al 2000).…”
Section: Lag (Xf) Correlatormentioning
confidence: 99%
“…Examples of recirculating lag correlators are described by Ball (1973) and Okumura et al (2000). The WIDAR correlator on the VLA uses recirculation (Perley et al 2009). …”
Section: Lag (Xf) Correlatormentioning
confidence: 99%
See 1 more Smart Citation